THE ESSENCE AND CAUSES OF THE ENTERPRISE DEVELOPMENT CRISIS - Е. В. Садченко (Ринкова економіка: сучасна теорія і практика управління, 2017)
The article considers the features of management during a crisis, as the organizational development background. It defines the essence of the problem and the crisis of company's development. Crisis of the company's development, which is closely connected with the nature of the enterprise life cycle, is represented in the paper. Identified approaches, principles and methods of crisis management.